Applying Erikson's Wisdom to Self-Management Practices of Older Adults: Findings From Two Field Studies. (April 2015) - Perry, Tam E.; Ruggiano, Nicole; Shtompel, Natalia; Hassevoort, Luke
According to Erik Erikson's theory on the stages of human development, achieving wisdom later in life involves revisiting previous crises and renewing psychosocial accomplishments. However, few studies have used Erikson's theory as a framework for examining how older adults self-manage physical and mental health changes that commonly occur later in life. This article presents findings from two qualitative studies that demonstrate how older adults apply wisdom in new domains. Specifically, it was found that older adults (1) reasserted autonomy by initiating creative problem solving and (2) applied skills gained from productive activities earlier in life to new health-related problems that arise later in life. These findings highlight the importance of engaging older adults to repurpose their life skills and thus reapply wisdom to new areas of their lives. Implications for practice are discussed.